Death Deterrent Effect for Corruptors : Implications Verdict Light Action Criminal Corruption (Qawanin Jurnal Ilmu Hukum, 2025)
This study aims to analyze the phenomenon of light sentences imposed on corruption perpetrators in Indonesia from the perspective of the theory of justice. In the context of corruption as an extraordinary crime, this study highlights the imbalance between the principles of retributive, distributive, and restorative justice and their implementation in the justice system. This normative legal research uses a regulatory, comparative, and conceptual approach, and analyzes data descriptively-prescriptively based on legal literature and reports from related international institutions. The results of the study indicate that light against corruption perpetrators is caused by a number of factors, including weak law enforcement, political intervention, lack of supervision of the judicial apparatus, and a culture of tolerance for corruption. These findings confirm that the application of the theory of justice in the Indonesian legal system is still far from ideal, with striking disparities in sentencing, especially for perpetrators from the elite compared to perpetrators from the ordinary community. In addition, light sentences have a significant impact on the low deterrent effect, loss of public trust in the legal system, and the negative perception of the international community towards Indonesia's commitment to eradicating corruption. This study recommends structural and institutional reforms that include harmonization of national regulations with international standards, increasing the capacity of law enforcement officers, and strengthening legal literacy in society to create a more just and effective legal system. With a comprehensive approach, it is hoped that the eradication of corruption in Indonesia can achieve more optimal results.